The Effect of Perceived Security and Trust Using Mobile Banking Payment Method (In Madagascar) - Vatsiniaina Tatamo Sahondra; Viola De Yusa (Prosiding International conference on Information Technology and Business (ICITB), 2022)
This study investigates the impact of perceived security and trust using mobile banking on market place. It examines the effect of mobile baking among service quality, customer behavior and buying decision. The findings of the study indicate that among the variables perceived security and perceived trust has significant impacts customer buying decision when shopping online. Moreover, the result expected will be indicate that perceived security had significant positive affect on trust. Service quality improved to be a significant impact on customer satisfaction and buying decision. Keywords—Mobile banking, security perception, trust perception, Intention to buy